Catalyst based on anatase / rutile mixed-phase TiO2 and preparation method and application thereof

The core-shell structured anatase/rutile mixed-phase TiO2 catalyst was synthesized by hydrothermal method, which solved the problems of crystal phase composition and surface defect structure limitations in existing TiO2 catalysts, and achieved efficient removal of volatile organic compounds, especially toluene, with higher degradation efficiency and stability.

CN120605704APending Publication Date: 2025-09-09NANJING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510805732.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-17
Publication Date
2025-09-09

AI Technical Summary

Technical Problem

The crystal phase composition and surface defect structure of existing TiO2 photocatalysts limit their catalytic activity, especially the low and disordered heterojunction interface density in commercial P25 catalysts, which leads to discontinuous charge transfer paths and makes it difficult to achieve efficient removal of volatile organic compounds (VOCs). At the same time, traditional methods make it difficult to accurately control the oxygen vacancy concentration and optimize the Ti-O bond in an air atmosphere.

Method used

A core-shell structured anatase/rutile mixed-phase TiO2 catalyst was synthesized by a hydrothermal method under specific conditions, and combined with low-temperature calcination to regulate the oxygen vacancy concentration, forming a clear spatial interface distribution, weakening the Ti-O bond to activate the surface lattice oxygen.

Benefits of technology

The efficiency and stability of the catalyst in photodegrading VOCs were significantly improved, achieving higher toluene degradation efficiency and mineralization rate. It is suitable for large-scale production, with a stable oxygen vacancy structure and excellent performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120605704A_ABST
    Figure CN120605704A_ABST
Patent Text Reader

Abstract

The invention provides a catalyst based on anatase / rutile mixed-phase TiO2 as well as a preparation method and application thereof, and the preparation method comprises the following steps: adding the anatase / rutile mixed-phase TiO2 catalyst with a core-shell structure into water, and then carrying out hydrothermal treatment in water to obtain the anatase / rutile mixed-phase TiO2 catalyst. Compared with a mixed-phase TiO2 catalyst obtained by previous research, the catalyst obtained by the method has the advantages that the oxygen vacancy structure is optimized, and the activation of surface lattice oxygen is realized, so that the efficiency and stability of degrading VOCs (Volatile Organic Compounds) are remarkably improved. The method disclosed by the invention has the characteristics of simple process, low cost and easiness in large-scale preparation, and can be widely applied to the field of environmental governance, in particular to degradation of volatile organic pollutants in air purification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of photocatalyst materials, and in particular relates to a catalyst based on anatase / rutile mixed-phase TiO2, and a preparation method and application thereof. Background Art

[0002] Volatile organic compounds (VOCs), common air pollutants, have become a significant environmental and health concern. Long-term exposure to VOCs not only poses a serious threat to the respiratory and central nervous systems but may also increase the risk of cancer. Therefore, the development of efficient air purification technologies to mitigate VOC pollution is urgent. Photocatalytic oxidation technology, due to its environmental friendliness, resource conservation, and ability to effectively remove low-concentration VOCs, offers a promising solution to this problem. The design and preparation of photocatalysts is central to its implementation.

[0003] TiO2 has become the most widely used photocatalyst for air pollutant degradation due to its cost-effectiveness, environmental friendliness, and excellent chemical stability. Research has shown that its catalytic activity is highly dependent on its crystal phase composition and surface defect structure. Compared to TiO2 with either a single rutile (R) or anatase (A) phase, mixed anatase / rutile TiO2 phases effectively promote electron-hole separation, thereby enhancing its oxidation performance. For example, the commercially available Degussa P25 catalyst, known for its mixed rutile and anatase phase structure, is a widely used standard photocatalyst. However, the random distribution of the two phases in commercial P25 results in a low and disordered heterojunction interface, leading to a dispersed internal electric field and discontinuous charge transport pathways, limiting further performance improvements. In contrast, heterojunction TiO2 with a well-defined spatial interface arrangement may possess a stronger ability to build an internal electric field, further enhancing catalytic performance.

[0004] Furthermore, the catalytic activity of TiO2 is closely linked not only to its crystal structure but also to its surface defect structure (oxygen vacancies). Research has found that introducing oxygen vacancies into TiO2 crystals effectively inhibits electron-hole pair recombination and provides more active sites, thereby improving catalytic performance. Furthermore, oxygen vacancies significantly reduce the reaction energy barrier of surface lattice oxygen, but their regeneration relies on the adsorption and activation of gas-phase oxygen by oxygen vacancies. To promote the dynamic "activation-regeneration" cycle of surface lattice oxygen and oxygen vacancies, it is necessary to optimize the oxygen vacancy structure to further weaken the Ti-O bond strength and achieve high utilization efficiency of surface lattice oxygen. Traditional methods for introducing oxygen vacancies, such as high-temperature hydrogen reduction, the use of strong reducing agents (such as NaBH4, Al, and CaH2), and elemental doping, often present difficulties in synthesis, high synthesis risks, and unstable oxygen vacancy introduction. More importantly, these methods struggle to precisely control the oxygen vacancy concentration in air and lack the ability to further optimize the Ti-O bonding near oxygen vacancies, limiting the dynamic activation efficiency of surface lattice oxygen.

[0005] In summary, developing a synergistic regulation method that can achieve both oxygen vacancy structure optimization and surface lattice oxygen activation is of great significance to promoting the practical application of efficient photocatalysts. Summary of the Invention

[0006] In view of the above problems, the present invention is based on the applicant's previous research ( Science of the Total Environment 924 (2024) 171521 ) on the basis of the present invention, a catalyst based on anatase / rutile mixed-phase TiO2 and its preparation method and application are provided. Compared with the mixed-phase TiO2 catalyst obtained in previous studies, the catalyst optimizes the oxygen vacancy structure and realizes the activation of surface lattice oxygen, thereby significantly improving its efficiency and stability in degrading VOCs (toluene).

[0007] To achieve the above object, the present invention adopts the following technical solutions: A method for preparing a catalyst based on anatase / rutile mixed phase TiO2 comprises the following steps: The anatase / rutile mixed phase TiO2 catalyst with a core-shell structure is added into water and subjected to hydrothermal reaction under closed conditions to obtain the catalyst.

[0008] The method for obtaining the anatase / rutile mixed phase TiO2 catalyst with a core-shell structure is a prior art method, which is described in Science of the Total Environment 924 (2024) 171521.

[0009] Preferably, the temperature of the hydrothermal reaction is 30-200°C.

[0010] Preferably, the hydrothermal reaction time is 1 to 12 hours.

[0011] Preferably, the anatase / rutile mixed phase TiO2 catalyst having a core-shell structure is prepared by the following steps: (1) Add TiCl4 solution to concentrated hydrochloric acid to obtain a yellow solution; (2) After the yellow solution and ethylene glycol solution are fully mixed, the mixture is reacted in a closed container at 120-200°C, and the crude product is obtained after centrifugation and washing; (3) calcining the crude product at 150-650° C. in an air atmosphere to obtain the anatase / rutile mixed phase TiO 2 catalyst having a core-shell structure.

[0012] Preferably, the mass concentration of the concentrated hydrochloric acid is 36% to 38%, more preferably 30%.

[0013] Preferably, the washing in step (2) is washing with ethanol and water respectively.

[0014] Preferably, the reaction time in step (2) is 2 to 6 hours.

[0015] Preferably, the heating rate of the calcination in step (3) is 4°C / min.

[0016] Preferably, the calcination time in step (3) is 2 to 5 hours.

[0017] The second object of the present invention is to provide a catalyst based on anatase / rutile mixed phase TiO2 prepared by the above preparation method.

[0018] The third object of the present invention is to provide the use of the anatase / rutile mixed-phase TiO2 catalyst prepared by the above preparation method in photocatalysis.

[0019] Preferably, the application is the degradation of VOCs.

[0020] The present invention synthesizes an anatase / rutile mixed-phase TiO2 catalyst with a core-shell structure through a hydrothermal method under specific reaction conditions. The catalyst has a clear spatial interface distribution structure and can effectively regulate the TiO2 oxygen vacancy concentration by adjusting the calcination temperature, thereby having excellent photocatalytic performance.

[0021] On this basis, the present invention further activates surface lattice oxygen through a hydrothermal reaction with the help of oxygen vacancy structure, and the obtained catalyst further improves the mineralization efficiency of photodegradation.

[0022] The present invention adjusts the reaction solution to be under strong acid conditions by concentrated hydrochloric acid, and strong acid is beneficial to Ti 4+ The core of the rutile phase is preferentially hydrolyzed; during the hydrothermal reaction, due to the presence of excess TiCl4, the water in the system will be consumed first, and Ti 4+The titanium precursor formed by chelation with ethylene glycol will undergo further condensation and dehydration reaction, gradually forming anatase phase on the outside of rutile. Therefore, the hydrothermally synthesized TiO2 presents a clear phase interface structure. In addition, due to the excess Ti 4+ The synthesized TiO2 has many unsaturated sites, which will form obvious lattice defects. High-temperature calcination will affect the lattice distortion and affect the oxygen vacancy concentration. Further hydrothermal treatment can weaken the Ti-O bond in TiO2, thereby increasing the surface lattice oxygen activity and significantly enhancing the VOCs removal rate and mineralization rate under the action of oxygen vacancies.

[0023] The beneficial effects of the present invention are: (1) The process of the present invention is simple to operate, the synthesis process is short, and it is suitable for large-scale production.

[0024] (2) In the present invention, by controlling the hydrolysis rate of TiCl4 in water and ethylene glycol, anatase / rutile mixed phase TiO2 with spatial interface distribution is synthesized, which is beneficial to the unidirectional transfer of electrons and effectively enhances the catalyst performance.

[0025] (3) The TiO2 prepared by the present invention can effectively control the oxygen vacancy concentration by low-temperature calcination in an air atmosphere, and the oxygen vacancy structure is more stable.

[0026] (4) The TiO2 crystals prepared by the present invention are uniform in size and have good crystallinity.

[0027] (5) The TiO2 prepared by the present invention can effectively weaken the Ti-O bond based on oxygen vacancies during hydrothermal treatment, thereby promoting more surface lattice oxygen to participate in the oxidation process of VOCs.

[0028] (6) The TiO2 prepared by the present invention has better degradation efficiency, mineralization rate and stability for VOCs such as toluene than the commercial P25 and the anatase / rutile mixed phase TiO2 catalyst with a core-shell structure in previous studies. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the XRD pattern of Test Example 1 (1).

[0030] Figure 2 This is the TEM image of T2 in Test Example 1 (1).

[0031] Figure 3 This is the EPR diagram in Test Case 1 (1).

[0032] Figure 4 This is a comparison chart of the toluene conversion efficiency of the catalyst in Test Example 1 (2) and commercial P25.

[0033] Figure 5This is a comparison chart of the selectivity of the catalyst of Test Example 1 (2) and commercial P25 for carbon dioxide.

[0034] Figure 6 This is the Raman graph of the catalyst of Test Example 1 (3).

[0035] Figure 7 This is the O2-TPD diagram of the catalyst of Test Example 1 (4).

[0036] Figure 8 This is the XRD pattern of Test Example 2 (1).

[0037] Figure 9 This is the EPR diagram in Test Case 2 (1).

[0038] Figure 10 This is a comparison chart of the conversion efficiency of the catalyst for toluene in Test Example 2 (2).

[0039] Figure 11 This is a comparison chart of the selectivity of the catalyst for carbon dioxide in Test Example 2 (2).

[0040] Figure 12 This is the Raman graph of the catalyst of Test Example 2 (3).

[0041] Figure 13 This is the O2-TPD diagram of the catalyst of Test Example 2 (4).

[0042] Figure 14 This is a correlation analysis diagram between the oxygen vacancy concentration of T3, T4, and T5 and the Raman shift after hydrothermal treatment.

[0043] Figure 15 This is a correlation analysis diagram between the Raman shift of T3, T4, and T5 and the surface lattice oxygen increment. DETAILED DESCRIPTION

[0044] The following detailed description of exemplary embodiments of the present invention refers to the accompanying drawings. Although these exemplary embodiments are described in sufficient detail to enable those skilled in the art to practice the invention, it should be understood that other embodiments may be implemented and various changes may be made to the invention without departing from the spirit and scope of the invention. The following more detailed description of the embodiments of the invention is not intended to limit the scope of the claimed invention, but is merely for illustrative and non-limiting description of the features and characteristics of the invention, to set forth the best mode for carrying out the invention and to enable those skilled in the art to practice the invention. Therefore, the scope of the invention is limited only by the appended claims.

[0045] Example 1 (1) Mix 1.7 mL of ultrapure water and 8.3 mL of concentrated hydrochloric acid to obtain 10 mL of HCl aqueous solution (30% HCl solution). (2) Add 10 mL of TiCl4 solution to step (1) and continue stirring at room temperature until a yellow solution is obtained; (3) Add 20 mL of ethylene glycol solution to step (2) and continue stirring at room temperature for 10 min to obtain a light yellow solution; (4) The light yellow solution obtained in step (3) was transferred to a 100 mL polytetrafluoroethylene stainless steel autoclave and placed in an oven for high temperature treatment at 160°C for 3 h; (5) After the solid obtained in step (4) is cooled to room temperature, it is centrifuged at 8000 rpm for 5 min, and then washed and centrifuged twice with ethanol and distilled water respectively. The obtained solid is placed in an oven and dried at 110°C for 8 h to obtain a crude product.

[0046] (6) The crude product obtained in step (5) was placed in a tube furnace, and the temperature was raised to 350° C. at a rate of 4° C. / min under air atmosphere and maintained for 2 h to obtain the catalyst TiO2-1.

[0047] (7) 2 g of the catalyst TiO2-1 obtained in step (6) was added to 50 mL of distilled water, transferred to a 100 mL polytetrafluoroethylene stainless steel autoclave, placed in an oven at 30°C for 1 h, cooled to room temperature, collected by centrifugation, and dried at 110°C for 8 h to obtain product T1.

[0048] Example 2 2 g of TiO2-1 obtained in Example 1 was added to 50 mL of distilled water, transferred to a 100 mL polytetrafluoroethylene stainless steel autoclave, placed in an oven for high-temperature treatment at 180° C. for 1 h, cooled to room temperature, collected by centrifugation, and dried at 110° C. for 8 h to obtain the product T2.

[0049] Example 3 2 g of TiO2-1 obtained in Example 1 was added to 50 mL of distilled water, transferred to a 100 mL polytetrafluoroethylene stainless steel autoclave, placed in an oven for high-temperature treatment at 180° C. for 5 h, cooled to room temperature, collected by centrifugation, and dried at 110° C. for 8 h to obtain the product T3.

[0050] Test Example 1 (1) The catalysts prepared in Examples 1-3 were characterized by XRD, TEM, and EPR. The results were as follows: Figure 1 、 2 , as shown in 3.

[0051] according to Figure 1X-ray diffraction (XRD) patterns of TiO2-1 and TiO2 from T1, T2, and T3 reveal diffraction peaks attributable to rutile (JCPDS No. 21-1276) and anatase (JCPDS No. 21-1272). Furthermore, after embedding and sectioning, transmission electron microscopy (TEM) was used to further investigate the spatial distribution of anatase and rutile at the TiO2 catalyst interface.

[0052] Figure 2 The TEM image confirmed that the synthesized T2 had a spherical structure of 2~3um. Only rutile phase nanoparticles existed in the core part of the photocatalyst, while anatase phase nanoparticles were all distributed on the outer surface of the catalyst, with a clear phase interface distribution structure.

[0053] Figure 3 From the electron paramagnetic resonance (EPR) spectrum, the symmetrical strong peak at g=2.003 corresponds to oxygen vacancies. It can be seen that the oxygen vacancy concentration of TiO2-1 and T1, T2, and T3 did not change significantly before and after hydrothermal treatment.

[0054] (2) Catalyst performance evaluation: The performance of each catalyst was tested under the conditions of reaction temperature of 30°C, catalyst mass of 40 mg, gas flow rate of 75 mL / min, toluene inlet concentration of 20 ppm, and relative humidity of 50%.

[0055] like Figure 4 、 5 As shown, the toluene conversion rate of TiO2-1 reached 75%, and the CO2 conversion rate reached 82%, far exceeding the 45% toluene conversion rate (CO2 conversion rate 73%) of commercial P25.

[0056] Catalysts T1, T2, and T3, also based on the TiO2-1 sample but prepared under different hydrothermal conditions, have toluene conversion rates of 82%, 90%, and 95%, respectively, and the corresponding CO2 selectivities are 84%, 87%, and 90%, respectively, indicating that the catalysts obtained by hydrothermal reaction have greatly improved the catalytic degradation performance of toluene compared with the anatase / rutile mixed-phase TiO2 catalyst.

[0057] (3) Raman spectroscopy of TiO2-1, T1, T2, and T3 Figure 6 ) analysis found that 143 cm −1 The peak at is the bending vibration peak of the Ti-O bond in the anatase phase. Based on Hooke's law, it was observed that the position of this peak red-shifted with the change of hydrothermal conditions (T1→T2→T3), indicating that the Ti-O bond gradually weakened, indicating that hydrothermal treatment can significantly weaken the Ti-O bond energy of TiO2 samples.

[0058] (4) In addition, the O₂-TPD spectra of TiO₂-1 and T1, T2, T3 ( Figure 7 ) show that a new lattice oxygen desorption peak appears at about 315 °C. The intensity of this peak increases significantly with the increase of hydrothermal temperature and time (T1 < T2 < T3), and this increasing trend is highly consistent with the improvement of toluene conversion rate and mineralization rate (CO₂ selectivity) of the samples. This confirms that the method of the present invention can effectively optimize the activity of surface lattice oxygen, thereby significantly improving the performance of the catalyst.

[0059] Example 4 (1) Mix 1.7 mL of ultrapure water and 8.3 mL of concentrated hydrochloric acid evenly to obtain 10 mL of HCl aqueous solution (30% HCl solution); (2) Add 10 mL of TiCl₄ solution to step (1), and continuously stir at room temperature until a yellow solution is obtained; (3) Add 20 mL of ethylene glycol solution to step (2), and continuously stir at room temperature for 10 min to obtain a light yellow solution; (4) Transfer the light yellow solution obtained in step (3) to a 100 mL polytetrafluoroethylene stainless steel autoclave, and place it in an oven for high-temperature treatment at 160 °C for 3 h; (5) After the solid obtained in step (4) is cooled to room temperature, centrifuge at 8000 rpm for 5 min, and then wash it twice with ethanol and distilled water respectively by centrifugation. The obtained solid is placed in an oven and dried at 110 °C for 8 h to obtain a crude product.

[0060] (6) Place the crude product obtained in step (5) in a tubular furnace, and heat it to 250 °C at a rate of 4 °C / min in an air atmosphere and hold for 2 h to obtain the catalyst TiO₂-4.

[0061] (7) Add 2 g of the catalyst TiO₂-4 obtained in step (6) to 50 mL of distilled water, transfer it to a 100 mL polytetrafluoroethylene stainless steel autoclave, place it in an oven for high-temperature treatment at 180 °C for 5 h, centrifuge and collect it after cooling to room temperature, and dry it at 110 °C for 8 h to obtain the product T4.

[0062] Example 5 (1) Mix 1.7 mL of ultrapure water and 8.3 mL of concentrated hydrochloric acid evenly to obtain 10 mL of HCl aqueous solution (30% HCl solution); (2) Add 10 mL of TiCl₄ solution to step (1), and continuously stir at room temperature until a yellow solution is obtained; ​(4) The light yellow solution obtained in step (3) was transferred to a 100 mL polytetrafluoroethylene stainless steel autoclave and placed in an oven for high temperature treatment at 160°C for 3 h; (5) After the solid obtained in step (4) is cooled to room temperature, it is centrifuged at 8000 rpm for 5 min, and then washed and centrifuged twice with ethanol and distilled water respectively. The obtained solid is placed in an oven and dried at 110°C for 8 h to obtain a crude product.

[0063] (6) The crude product obtained in step (5) was placed in a tube furnace, and the temperature was raised to 450° C. at a rate of 4° C. / min under air atmosphere and maintained for 2 h to obtain the catalyst TiO2-5.

[0064] (7) 2 g of the catalyst TiO2-5 obtained in step (6) was added to 50 mL of distilled water, transferred to a 100 mL polytetrafluoroethylene stainless steel autoclave, placed in an oven for high-temperature treatment at 180°C for 5 h, cooled to room temperature, collected by centrifugation, and dried at 110°C for 8 h to obtain the product T5.

[0065] Test Example 2 (1) The catalysts prepared in Examples 4 and 5 were characterized by XRD and EPR. The results were as follows: Figure 8 、 9 shown.

[0066] according to Figure 8 The XRD patterns of TiO2-4, TiO2-5, T4, and T5 all showed similar mixed phase ratios, indicating that the calcination temperature only affected the crystallinity of TiO2. In addition, according to Figure 9 The electron paramagnetic resonance (EPR) of the TiO2 photocatalyst shows a strong symmetrical peak at g=2.003 corresponding to oxygen vacancies. It can be seen that the calcination temperatures of 250℃ and 350℃ will produce different concentrations of oxygen vacancies, and there is no obvious change in the oxygen vacancy concentration before and after hydrothermal treatment.

[0067] (2) Catalyst performance evaluation: The performance of each catalyst was tested under the conditions of reaction temperature of 30°C, catalyst mass of 40 mg, gas flow rate of 75 mL / min, toluene inlet concentration of 20 ppm, and relative humidity of 50%.

[0068] like Figure 10 、 11 As shown in Figure 2, the toluene conversion rate of T4 reached 60.2%, and the CO2 conversion rate reached 91%. The toluene conversion rate of T5 reached 65.5%, and the CO2 conversion rate reached 74%.

[0069] (3) Raman spectroscopy was performed on TiO2-4, TiO2-5, T4 and T5. Figure 12) analysis found that 143 cm −1 The peak at 143 cm is the bending vibration peak of the Ti-O bond in the anatase phase. According to Hooke's law, T4 relative to TiO2-4 and T5 relative to TiO2-5 are both found at 143 cm −1 The red shift of the peak, the greater the red shift value of the Ti-O bond, the more significant the improvement in toluene degradation performance. These results show that the method of the present invention can weaken the strength of the Ti-O bond in the anatase phase, thereby improving the catalytic performance of toluene degradation.

[0070] (4) O2-TPD characterization of TiO2-4, TiO2-5, T4, and T5 Figure 13 As shown in Figure 2, a new surface lattice oxygen peak was detected around 315°C in both T4 and T5 samples. The area of ​​the surface lattice oxygen peak increased in all hydrothermally treated TiO2 samples, indicating that the weakening of the Ti-O bond facilitates the activation of lattice oxygen, thereby significantly improving the mineralization rate of toluene degradation. Notably, a higher oxygen vacancy concentration is more conducive to the activation of surface lattice oxygen during hydrothermal treatment.

[0071] (5) If Figure 14 As shown in the figure, there is a good linear correlation between the Ti–O bond displacement caused by hydrothermal treatment and the oxygen vacancy concentration, indicating that the change in the Ti–O bond structure is significantly affected by oxygen vacancies. Furthermore, the displacement of the Ti–O bond will lead to an increase in its bond length, thereby significantly reducing the activation energy barrier of lattice oxygen and facilitating the generation of lattice oxygen. This phenomenon is also consistent with Figure 15 The correlation between the Ti–O bond displacement and the surface lattice oxygen increment is consistent.

[0072] Based on these results, the TiO2 material prepared by this invention can be calcined at different temperatures to control the generation of oxygen vacancies, while subsequent hydrothermal treatment can further stimulate the activity of surface lattice oxygen based on the oxygen vacancy concentration and treatment parameters. Therefore, developing a control strategy that can synergistically optimize the oxygen vacancy structure and enhance surface lattice oxygen activation is of great significance for promoting the practical application of high-efficiency photocatalysts.

Claims

1. A method for preparing a catalyst based on anatase / rutile mixed phase TiO2, characterized in that: The steps include: The anatase / rutile mixed phase TiO2 catalyst with a core-shell structure is added into water and subjected to hydrothermal reaction under closed conditions to obtain the catalyst.

2. The preparation method according to claim 1, characterized in that The temperature of the hydrothermal reaction is 30-200°C.

3. The preparation method according to claim 1, characterized in that The hydrothermal reaction time is 1 to 12 hours.

4. The preparation method according to claim 1, characterized in that The anatase / rutile mixed phase TiO2 catalyst with a core-shell structure is prepared by the following steps: (1) Add TiCl4 solution to concentrated hydrochloric acid to obtain a yellow solution; (2) After the yellow solution and ethylene glycol solution are fully mixed, the mixture is reacted in a closed container at 120-200°C, and the crude product is obtained after centrifugation and washing; (3) calcining the crude product at 150-650° C. in an air atmosphere to obtain the anatase / rutile mixed phase TiO 2 catalyst having a core-shell structure.

5. The preparation method according to claim 4, characterized in that The mass concentration of the concentrated hydrochloric acid is 36% to 38%, more preferably 30%.

6. The preparation method according to claim 4, characterized in that The washing in step (2) is washing with ethanol and water respectively.

7. The preparation method according to claim 4, characterized in that The reaction time in step (2) is 2 to 6 hours.

8. The preparation method according to claim 4, characterized in that The calcination time in step (3) is 2 to 5 hours.

9. A catalyst based on anatase / rutile mixed phase TiO2 prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the anatase / rutile mixed-phase TiO2 catalyst prepared by the preparation method according to any one of claims 1 to 8 in photocatalysis.